Implementasi Perda Kabupaten Sambas Nomor 4 Tahun 2020 Tentang Pelayanan Publik dalam Menerapkan Prinsip Good Governance di Kantor Camat Pemangkat - Utari Dwi Putri (Jurnal Global Futuristik, 2025)
This research is motivated by the importance of implementing the principles of Good Governance in the provision of public services at the sub-district level, as mandated in Sambas Regency Regional Regulation Number 4 of 2020. The Pemangkat Sub-district Office as the implementer of public services has the responsibility to implement the principles of good governance such as transparency, accountability, responsiveness, effectiveness, efficiency, and the rule of law. The purpose of this study is to determine how the implementation of Regional Regulation Number 4 of 2020 at the Pemangkat Sub-district Office, identify obstacles encountered in its implementation, and describe strategies undertaken to improve the quality of public services. This study uses a qualitative method with an empirical normative approach, and data collection through observation, interviews, and documentation. The results of the study indicate that the implementation of the Regional Regulation has begun to run with several indicators such as the installation of service flows, the preparation of SOPs, and increasing employee professionalism. However, there are still shortcomings such as the lack of available service information, limited facilities, and the absence of a formal complaint system. The obstacles faced include structural barriers, such as a lack of infrastructure and limited budgets, as well as cultural barriers such as a lack of public understanding of the contents of regional regulations and minimal public participation. Strategies implemented include utilizing information technology through websites and social media, increasing employee capacity, and service innovations such as the outreach program in collaboration with the Population and Civil Registration Office (Disdukcapil). Future efforts are directed at developing digital applications and public complaint forums to make services more inclusive, efficient, and equitable.